Composite steel and concrete design comparison of international codes - Blassoples, G W (Department of Civil Engineering, 2026)
The theme of this thesis is the comparison of design methodology for composite steel concrete beam members as permitted by four selected international design Codes. The investigation was necessitated by the considerable difference in complexity of and results obtained in the application of methods specified by the latest international design Codes for determining the design moment and moment capacity of composite beams.